Gadolinium Enhancement Is Not Associated With Disc Inflammation in Patients With Sciatica. Issue 12 (15th June 2019) - Djuric, Niek; Yang, Xiaoyu; Barzouhi, Abdelilah el; Ostelo, Raymond W.J.G.; Duinen, Sjoerd G. van; Nijeholt, Geert J. Lycklama à; van der Kallen, Bas F.W.; Peul, Wilco C.; Vleggeert-Lankamp, Carmen L.A.
Abstract : Study Design: Retrospective observational histological study. Objective: To evaluate the reliability of gadolinium enhancement as a marker for inflammation by associating gadolinium enhancement findings with the degree of inflammation as measured by macrophage infiltration in disc material retrieved during disc surgery in patients with sciatica. Summary of Background Data: Disc inflammation often occurs in sciatica patients, a noninvasive tool that is used to assess disc inflammation is Gadolinium enhanced MR imaging. Methods: Disc tissue was retrieved from patients in the Sciatica trial (N = 119), a multicenter randomized controlled trial in patients with sciatica. Disc tissue was embedded in paraffin and stained with hematoxylin and CD68. Tissue samples were categorized as mild (0–10 macrophages/cm 2 ), moderate (10–100 macrophages/cm 2 ), and considerable (>100 macrophages/cm 2 ) inflammation. Of the 119 MRIs, 96 were additionally performed with contrast-enhanced gadolinium. Results: Seventy-four patients showed gadolinium enhancement of the disc herniation and 26 of the nerve root. Degree of inflammation by macrophages was not associated with gadolinium enhancement of nerve roots or herniated discs. These results did not change if the patient groups with and without Modic type 2 changes were evaluated separately. Furthermore, no associations were observed between gadolinium enhancement and presence of Modic type 2 changes. Conclusion: This study found gadolinium enhanced MRI findings to be unreliable as an indicator for inflammation of disc herniation or nerve root in patients with sciatica. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the textIn a population of 119 patients with lumbar disc herniations, study found sought to associate gadolinium enhancement of the herniated disc and nerve root with histologically defined inflammation of the herniated disc. In addition, these associations were tested in patients with and without Modic. No associations were found.